A COMPARATIVE ANALYSIS OF BOOST CONVERTER TOPOLOGIES FOR PHOTOVOLTAIC SYSTEMS USING MPPT (PO) AND BETA METHODS UNDER PARTIAL SHADING (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Photovoltaic systems have become a popular renewable energy source due to their many benefits. Optimizing PV systems requires efficiently extracting the maximum power point. This can be achieved by optimizing maximum peak power tracking algorithms or testing different PV system topologies.  In this paper, different topologies of dc/dc converters with two MPPT algorithms (Beta and perturb and observe) are tested to control the duty ratio of the converters.  At first, the modeling of different DC/DC converter topologies to optimize the maximum power point tracking efficiency of photovoltaic systems is achieved. The simulation results show that the Beta algorithm gives a higher accuracy and efficiency than the P&O algorithm, especially in low oscillations with fast convergence speed. According to the findings, a parallel arrangement of boost converters is usually preferable to a series arrangement, especially for following changes in irradiance.
Keywords: Photovoltaic (PV) system; Maximum Power Point Tracking (MPPT); Dc-dc converter; Topologies; Beta method